Vaccination attitude assessment among attendees the birthing preparation course: a pre-post study. (30th September 2020) - Di Pilla, A; Bruno, S; Carini, E; Beccia, V; Quaranta, G; La Milia, D; Masini, L; Carducci, B; Lanzone, A; Laurenti, P
Abstract: Background: Vaccinations are among the most effective and safe ways to prevent the spreading and the complications of infectious diseases. In order to reduce risks and to protect children from the early beginning of their life, most vaccinations are recommended within the 15th month of life. In Italy, the law provides 10 compulsory vaccinations to the 0-16 age group. A training program was carried on by a Public Health specialist during the birthing preparation course, aimed at increasing the attitude to vaccination in maternal-child age. Methods: A training session in the birthing preparation course was specifically carried out to raise awareness about vaccination during both pregnancy and puerperium and in early childhood; a questionnaire on vaccination awareness was administered before and after the training session. Results: Out of 119 pregnant women attended the birthing preparation course from October 2019 to January 2020. As a result of the interventions, the percentage of the participants who consider the preparatory course a useful tool to obtain information about vaccines increases significantly from 30.34% pre-intervention to 64.56% post-intervention (p < 0.001). There is a significant increase in the mean number of vaccinations that the participants want their children to get, out of the 12 vaccinations proposed in the questionnaire: 9.68/12 pre-intervention versus 10.57/12 post-intervention (p = 0.021). Participants supporting the mandatory vaccinations are 96.04% pre-intervention and rise to 98.73% post-intervention. Conclusions: Attitude and knowledge related to vaccination are crucial values for maternal-child health: they significantly increased after a training session dedicated to vaccination as a part of the pregnant pre-birth course, whose aim can be therefore extended to the management of the health of the child, well beyond the period of pregnancy, labor and childbirth, according the life-course approach to health, from the Public Health perspective. Key messages: The childbirth preparation courses for pregnant should be valuable as a precious opportunity to raise parents' awareness and their attitude to vaccinations, if dedicated sessions are included in them. The mandatory nature of vaccines is very well received by pregnant women.